Land use impact on soil erosion at different scales in the Brazilian semi-arid - Santos, Julio Cesar; Andrade, Eunice; Medeiros, Pedro Henrique; Guerreiro, Maria João; Palácio, Helba (Revista Ciência Agronômica, 2016)
Erosion and sediment transport processes are strongly dependent on the spatial scale and land use. The objective of this study is to analyse the effects of slash and burn of vegetation followed by grass cultivation for grazing, on the hydrological and sedimentological behaviour at different spatial scales in a semiarid region in Brazil. Rainfall, runoff and soil loss were measured during three years (total of 116 rainfall-runoff events) at three spatial scales: 1 m² and 20 m² plots and 2.8 ha watershed. During the first year (2009) the native dry tropical forest/Caatinga vegetation was maintained, whereas on the following years (2010 and 2011) the original vegetation was cleared using slash and burn techniques to grow pasture (Andropogon gayanus Kunt). Annual runoff coefficient is highest at the 20 m² plot among the investigated scales. Runoff presented the same trend in all years. Sediment yield was strongly influenced by the land cover. Slash, burn and pasture cultivation strongly impacted sediment yield: the first two events after the land cover change yielded roughly ten times more sediment than similar events in the years with native cover and after grass development. The change was most noticeable at the catchment scale due to erosion along the stream, redefining the drainage network.